The due diligence handbook : corporate governance, risk management and business planning - Spedding, Linda S. , 1952- (Amsterdam ; Oxford : CIMA, 2009)
Features information on legislation, primary sources, codes and best practice guidance. This work combines various matters concerning corporate governance with due diligence issues and in doing so provides you with the information and tools you need to help you protect your business when under taking due diligence
Includes bibliographical references
Keywords: Business planning; Corporate governance -- Law and legislation -- Great Britain; Risk management